Psychological aggression, attitudes about violence, violent socialization, and dominance in dating relationships - Esquivel Santoveña, Esteban Eugenio (2019)
Psychological aggression is a widespread form of abuse in dating relationships, especially in collectivist societies with ties to patriarchal beliefs. Despite the prevalence of psychological aggression, it has seldom been studied in connection with known antecedents of interpersonal violence, including dominance, attitudes supportive of violence, and violence socialization processes during childhood. The present study sought to test relationships among these variables in young men and women. A total of 500 Mexican undergraduate students in northern Mexico reported on their experiences with psychological aggression, the dominance of a dating partner, and violent socialization during childhood, as well as on their approval of violence within and outside the family. The results indicate that the dominance of a dating partner is directly linked to male and female intimate partner violence (IPV) perpetration. Violent socialization and proviolent attitudes appear to be related to female dominance. Female and male psychological aggression victimization was predicted by the participant’s own perpetration. In general, a dyadic approach appears to be useful for explaining psychological aggression perpetration and victimization in a collectivist society, in light of recent changes in normative beliefs held by young educated Mexicans. Implications for future research and public policy are discussed.